2019
DOI: 10.5964/jspp.v7i2.865
|View full text |Cite
|
Sign up to set email alerts
|

The role of identity transformations in comparative victim beliefs? Evidence from South Sudanese diaspora

Abstract: There has been a growing interest in the study on collective victimhood and this research has increased our knowledge on how victim groups construe their victimization relative to other groups. However, most of this research has assumed that the groups involved in these construals were pre-existing prior to the conflict and remained fixed during and after the conflict. This study aimed to examine how conflict facilitates the transformation of social identities (i.e., how ingroups and outgroups are construed) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…Our study extends this focus and examines comparative victim beliefs linked with intersecting identities that are relevant to intergroup relations. Our findings revealed two comparative victim beliefs that have not yet received much attention in the literature (Noor et al, 2017): downward comparisons that convey beliefs of privilege, and qualitative differences in experiences of collective victimization (but see Nair & Vollhardt, 2019;Twali, 2019). Adding these collective victim beliefs to the more commonly assessed measures of competitive victimhood and inclusive victim beliefs will help expand the narrow range of collective victim beliefs that are currently the focus of the (quantitative) literature on this topic, and come closer to a fuller representation of the various complex ways in which people make sense of their own and other groups' experiences of oppression.…”
Section: Theoretical Contributions and Future Directionsmentioning
confidence: 77%
“…Our study extends this focus and examines comparative victim beliefs linked with intersecting identities that are relevant to intergroup relations. Our findings revealed two comparative victim beliefs that have not yet received much attention in the literature (Noor et al, 2017): downward comparisons that convey beliefs of privilege, and qualitative differences in experiences of collective victimization (but see Nair & Vollhardt, 2019;Twali, 2019). Adding these collective victim beliefs to the more commonly assessed measures of competitive victimhood and inclusive victim beliefs will help expand the narrow range of collective victim beliefs that are currently the focus of the (quantitative) literature on this topic, and come closer to a fuller representation of the various complex ways in which people make sense of their own and other groups' experiences of oppression.…”
Section: Theoretical Contributions and Future Directionsmentioning
confidence: 77%
“…Whether or not members of the victim group acknowledge these actions and attribute some responsibility for the violence to ingroup members may vary. For example, nearly half of the participants of a qualitative study among Sudanese refugees who had lived through the civil war reported actions of ingroup members that contributed to harming their group in different ways, while more than half did not (Twali, ).…”
Section: Construals Of Collective Violence Among Victim and Perpetratmentioning
confidence: 99%
“…Here, we simply wish to emphasize that, although the effects of inclusive victim consciousness can be understood theoretically as prosocial effects of shared, superordinate identities on intergroup outcomes (Dovidio et al 2009), the inclusion of other groups in a shared category of "victims of violence and oppression" may be particularly powerful in the context of ongoing violent conflicts and in post-violence transitional justice settings, in comparison to other superordinate identities and social categories that practitioners may use in interventions aimed at fostering peace and social change. In other words, it is not just the boundaries of the group identity that matter but also the content of this shared identity (see also Twali 2019).…”
Section: What Inclusive Victim Consciousness Is Notmentioning
confidence: 99%
“…It is crucial to critically examine the reference points and identities that create the basis for inclusive victim narratives. Most research examining this topic focus on singular identities such as ethnicity, nationality, religion or race, which are also often the fault lines of conflict and group-based violence (Nair and Vollhardt 2019;Twali 2019). However, social identities as well as social roles within identity groups are complex and fluid.…”
Section: Challenges In Defining the Reference Points For Inclusive Victim Narrativesmentioning
confidence: 99%